Advanced technologies for satellite navigation and geodesy. Issue 6 (15th September 2019) - Giorgi, G.; Schmidt, T.D.; Trainotti, C.; Mata-Calvo, R.; Fuchs, C.; Hoque, M.M.; Berdermann, J.; Furthner, J.; Günther, C.; Schuldt, T.; Sanjuan, J.; Gohlke, M.; et al.
Abstract: This manuscript reviews recent progress in optical frequency references and optical communication systems and discusses their utilizations in global satellite navigation systems and satellite geodesy. Lasers stabilized with optical cavities or spectroscopy of molecular iodine are analyzed, and a hybrid architecture is proposed to combine both forms of stabilization with the aim of achieving a target frequency stability of 10 -15 [s/s] over a wide range of sampling intervals. The synchronization between two optical frequency references in real-time is realized by means of time and frequency transfer on optical carriers. The technologies enabling coherent optical links are reviewed, and the development of an optical communication system for synchronization, ranging and data communication in space is described. An infrastructure exploiting the capabilities of both optical technologies for the realization of a modernized constellation of navigation satellites emitting highly synchronized signals is reviewed. Such infrastructure, named Kepler system, improves satellite navigation in terms intra-system synchronization, orbit determination accuracy, as well as system monitoring and integrity. The potential impact on geodetic key parameters is addressed.